Catechins promoted Enterococcus faecalis to alleviate related indices of nonalcoholic steatohepatitis mice induced by high-fat diet - Ying Zhang; Yaqin Zhou; Ming Zhou; Xiao Guan (Food Science and Human Wellness)
This study provides different opinion for exploring the mechanism of catechin (CAT) relieving nonalcoholic steatohepatitis (NASH), it is more innovative to explore from the perspective of intestinal microorganism. Through in vitro fermentation experiments, CAT could improve the abundance of Enterococcus, and Enterococcus faecalis (EF) accounts for the vast majority of Enterococcus in human gut. The experimental results in vivo showed that EF group and CAT + EF group could reduce the body weight, liver index and epididymal fat index of NASH mice, and improve the changes of serum and liver indexes. Hematoxylin-eosin staining observation showed that these two groups have greatly improved the fatty degeneration, balloon degeneration and necrotic focus caused by NASH. The alleviation of CAT + EF group was more obvious. Results of targeted metabonomics showed that CAT could promote EF to produce more methyl palmitate (C16:0), which plays a great role in relieving NASH. Our results indicated that EF could alleviate NASH and CAT + EF group had better alleviation may due to more production of methyl palmitate (C16:0) by EF. This study provides a new idea for CAT to alleviate NASH.